2008
DOI: 10.1016/s1658-3876(08)50007-0
|View full text |Cite
|
Sign up to set email alerts
|

S-phase fraction as a useful marker for prognosis and therapeutic response in patients with aplastic anemia

Abstract: Independently of the peripheral blood count, the SPF at diagnosis may provide information on the expected response to immunosuppressive therapy and the propensity for disease to evolve into MDS/AML. Hence, SPF may serve as an early indicator for the evolution of MDS/AML in patients with AA and thus contribute to therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…SPF is considered as an additional objective parameter for predicting the therapeutic response. A large number of studies have demonstrated the prognostic significance of FC analyses of SPF in many cancer types [42,43]. Smets et al reported that ALL patients with SPF…”
Section: Discussionmentioning
confidence: 99%
“…SPF is considered as an additional objective parameter for predicting the therapeutic response. A large number of studies have demonstrated the prognostic significance of FC analyses of SPF in many cancer types [42,43]. Smets et al reported that ALL patients with SPF…”
Section: Discussionmentioning
confidence: 99%
“…Circulating hematopoietic progenitors were shown to increase more dramatically in younger patients after cardiopulmonary bypass graft than in older patients, and advanced age was associated with impaired coronary microvascular response to vascular endothelial growth factor (VEGF) [29]. Conversely, advanced age has been associated with a higher S-phase fraction of circulating HSCs in patients with aplastic anemia, but this predisposed them to dysplasia and conversion to acute myeloid leukemia, indicative of abnormal HSC function [30]. Studies of adult stem cell isolation yield in elderly individuals have shown that equivalent numbers of adipose-derived mesenchymal stem cells (MSCs) can be isolated from older individuals undergoing vascular surgical procedures as from young, healthy individuals [31,32].…”
Section: Adults Stem Cells and Causes Of Agingmentioning
confidence: 99%
“…35 Conversely, advanced age has been associated with a higher S-phase fraction of circulating HSCs in patients with aplastic anemia, but this predisposed them to dysplasia and conversion to acute myeloid leukemia, indicative of abnormal HSC function. 36 Studies of adult stem cell isolation yield in elderly individuals have shown that equivalent numbers of adipose-derived MSCs can be isolated from older individuals undergoing vascular surgical procedures as from young, healthy individuals, 37,38 but the question remains whether those cells can be adequately expanded in tissue culture and whether they are able to mobilize, proliferate, and effect tissue repair in vivo when they are needed. In fact these same studies have shown that while advanced age does not impact availability of stem cells, fat from patients with diabetes yielded significantly fewer stem cells than fat from non-diabetic patients, suggesting that stem cells in the context of aging should probably be considered distinctly from stem cells in the context of diseases of aging.…”
Section: Adult Stem Cells and Diseases Of Agingmentioning
confidence: 99%